Cost and Returns on Chewing Stick Processing in Southwest Nigeria - Olawumi, Akinyode Timothy; Oluwalana, S. A, S. A; Momoh, S; Aduradola, A. M (American Journal of Human Ecology, 2013)
This study examined chewing stick processing in Ogun and Oyo states of Nigeria. Primary data were obtained from a cross-sectional survey of 50 chewing stick processors. The respondents were selected using purposive sampling technique. Data was collected on respondents’ socio-economic characteristics, resource use, costs, outputs, prices as well as the type of chewing stick processed. The data were analysed using descriptive statistics and budgetary analysis. Majority of the chewing stick processors (68.00%) are under the age of 45years, with the female-folk accounting for 60.00%. Most of the chewing stick processors (67.00%) had not more than primary school education. About 96% of the processors have been in the business for over 5 years. A typical medium-scale processor annually handled an average of 720 bundles of chewing stick valued at N6,480,000 ($4,050), and processed these at a cost of N6,105,350($38,158.44) to earn an average of N388,000($2,425) profit. The study concludes that chewing stick processing is a lucrative business that offers a source of livelihood for the respondents though it is presently import-dependent. Regional collaboration should be put in place for countries with comparative advantage in chewing stick cultivation to specialize in its production and export it to other countries thereby creating a virile international trade in it.The study recommends government intervention through domestication of chewing stick plants and provision of facilities such as roads, markets, stable electricity and appropriate machinery to enhance the scale of operation and efficiency.